Impact of reserve hoarding on external debt in financially underdeveloped emes - (:unkn) unknown (National Academy of Management, 2011)
The paper investigates 3 decades of the long run equilibrium relationship and Granger causality between foreign exchange reserves and external debt of the EMEs which are at different levels of financial development. The results of the bounds test for cointegration within the ARDL modeling approach of Pesaran et al. (2001) depict the long run equilibrium relationship between foreign exchange reserves and external debt of the concerned EMEs. The Granger causality analyses under VEC and VAR models demonstrate that reserves stockpiling may increase external debt in countries with low financial development level. This result reveals that Asian and Latin American EMEs with low levels of financial development should firstly develop their financial markets. © Imre Ersoy, 2011.
Keywords: Bounds test; Foreign exchange reserves; Granger causality; International lending and debt problems; Short term capital movements